SPIRULINA AS A PROMISING BIOLOGICALLY ACTIVE ADDITIVE FOR ADVANCED HEALTHY FOOD PRODUCTS - M. V. Kaledina; A. N. Fedosova; I. A. Bajdina; N. P. Shevchenko; L. V. Voloshenko (Современная наука и инновации, 2022)
Attention is drawn to the urgent need to search for new sources of substances for the development of innovative food products that can increase the adaptive potential of the organism. Modern man lives and works against a background of high neuro-emotional overload and not always favorable ecology, which stimulates scientists and food manufacturers to search for new sources of substances that can increase the resistance of the human body to the conditions of reality. Recently, microalgae have attracted the attention of the food industry. They have a number of prospects for application in the field of functional food products both in the form of natural biomass (microstructured powders or syrups) and the possibility of obtaining biologically active ingredients from them.